Do survey-based expectations mimic inflation in Nigeria? - Adamu Ibrahim (CBN Journal of Applied Statistics, 2015)
Survey-based expectations are mostly used by monetary authorities for inflation forecasts and evaluation of the credibility of their inflation fighting policies. It is also an important link in the monetary policy transmission mechanism. This study examined the predictive ability of business expectations survey (BES) inflation index on movements of inflation as well as the relationship between BES indicators and selected macroeconomic indicators in Nigeria. The study employed the modified Kaminsky-Reinhart (KLR) Signal Approach, correlation and trend analyses. The results of the modified KLR approach showed that BES inflation index predicts inflation rate only between 5 to 20 per cent threshold, which corresponds with Nigeria inflation series covered by the study. The paper found a weak and statistically insignificant relationship between the BES indicators and the selected macroeconomic indicators (inflation rate, exchange rate and lending rate). The study recommended that BES confidence indicators should be employed with some level of caution in making decision since the precision of its predictive ability is only moderate.
Keywords: E31; D84; 330; Business Confidence; expectations survey; forecasting; inflation